Feasibility study of starting a shuttle service from Johor Bahru to Desaru / Mohd Riza Abdul Halim - Abdul Halim, Mohd Riza (1989)
Transportation plays an important role in the development of a country and to the human activities. Malaysia as a developing country realises the needs -For adequate supply of transport services and system, and a wel 1-organised infrastructure -for the benefit of safe and economical bussiness activities and better communication. The nation's economic growth, and the improvement in the standards o-f living very much depend on the level of the transportation service.